Investigação da reação de Morita-Baylis-Hillman em reator de micro-ondas usando aldeídos aromáticos e isatina como eletrófilos: avaliação da atividade citotóxica em linhagem de células de leucemia promielocítica humanas (HL-60). - Lima Junior, Claudio Gabriel (2012)
In this work, we describe the investigation of the Morita-Baylis-Hillman reaction in microwave reactor, under closed vessel conditions to prepare 40 adducts, six novel, using 30 aromatic aldehydes and isatin as electrophiles and acrylonitrile (62a) , methyl acrylate (2), hydroxyethyl acrylate (62b), 2,2-dimethyl-1 ,3-dioxalyl acrylate (62c) and 2,3-dihydroxypropyl acrylate (62d) as Michael acceptors catalyzed by 1, 4-diazabicyclo [2.2.2] octane (DABCO). Most adducts were synthesized efficiently in short reaction times and excellent yields (70-99%) using this reaction protocol. However, this synthetic methodology showed limitations for less reactive substrates due to formation of byproducts and in some cases the formation of the desired adduct was not obtained. The application of low temperatures and / or conventional room temperature protocol led to the adducts preparation in a chemoselective manner. We proved that the formation of 2-hydroxy (4-bromophenyl) methyl acrylate (43) is reversible at 120 ° C, which explains the restriction observed in the preparation of certain adducts using heating by microwave irradiation and successfully protocol employing temperature of 0º C. Preliminary evaluation of cytotoxic activity against cell lines of human leukemia HL-60 was performed, where the nitrilated isatin derivatives adducts (56a and 56b) were the most active. Preliminary studies of antimitotic activity in embryonic cells of sea urchin (Echinometra lucunter) performed with nitrilated adducts containing pyridine rings (49, 47, 20), nitro group (16, 38, 15) and bromine atom attached to the aromatic ring (42) revealed that except 47, all investigated adducts strongly inhibited stages of embryonic development of the first cleavage and morula. Moreover, experimental observations showed no inhibition of microtubule organization, induction of cell necrosis and toxicity of the adducts, suggesting that the blocking mechanism of action of protein synthesis and / or DNA.